CEP stability of high-power few-cycle fiber lasers - Shestaev, E.; Hädrich, S.; Hoff, D.; Just, F.; Kienel, M.; Eidam, T.; Becker, N. C.; Eilenberger, F.; Klenke, A.; Müller, M.; Gottschall, T.; Drozdy, A.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
We characterize the carrier-envelope phase noise of the ELI-ALPS HR1 laser system emitting 100 W of average power, 1 mJ of pulse energy and <7 fs pulses. Contributions of individual components and technological solutions to carrier-envelope phase noise are analyzed.
CRIS-Team Scopus Importer:2023-04-20